Diversity and catching size of grouper fish (Serranidae) in coastal zone waters of Khanh Hoa province - Quang, Vo Van; Hoa, Tran Thi Hong; Thao, Le Thi Thu; Thinh, Tran Cong (Academia Journal of Biology, 2015)
The serranid species composition of the family Serranidae recorded in coastal areas of Khanh Hoa are  diverse with 36 species of 11 genera, which is 72% of the grouper species known from the coral reef of Vietnam (50 species), 50% of the known species from Vietnam's sea waters (72 species) and 29% of known grouper species from the East sea (126 species). Additionally, the genus Epinephelus  is the most diverse with 18 species, of those in Nha Trang bay were recorded  28 species, Van Phong - Ben Goi Bay: 17 species; Nha Phu Lagoon - Binh Cang: 8 species, and Cam Ranh - Thuy Trieu: 5 species. The groupers recorded from Khanh Hoa waters are more diverse compared with that from northern waters, such as Quang Ninh and coastal zone of North Central areas. The serranid species (groupers)  recorded in coastal areas of Khanh Hoa have a high similarity with the reef south central coastal zone, coral reef's Spratly Islands, coral reefs of Vietnam. However, it is lower levels of homologous regions in the north, such as Quang Ninh, coastal waters of the North Central coastal zone, Hong Kong and Taiwan. Of the total groupers caught, the serranid species commonly caught in Nha Trang bay are Blacktip grouper (Epinephelus fasciatus) accounted for 36%, Chocolate Hind (Cephalopholis boenak) is 25% and species Honeycomb grouper (E. merra) is 22%. The length of groupers caught is generally targeted in small species and juveniles (unmature size) of large species as Yellow grouper (Epinephelus awoara), Duskytail groupe (E. bleekeri), Leopard coral grouper (Plectropomus leopardus).